SMARCC1 Enters the Nucleus via KPNA2 and Plays an Oncogenic Role in Bladder Cancer - Wei, Zhengmao; Xu, Jinming; Li, Weiqing; Ou, Longhua; Zhou, Yingchen; Wang, Yan; Shi, Bentao (Frontiers in Molecular Biosciences, 2022)
Background: SWI/SNF-related, matrix-associated, actin-dependent regulator of chromatin subfamily C member 1 (SMARCC1), a component of the SWI/SNF complex, is thought to be an oncogene in several kinds of cancer. Materials and methods: The potential interaction between SMARCC1 and KPNA2 was inquired by Spearman’s correlation analysis, immunofluorescence staining and co-immunoprecipitation (Co-IP) assays. The immunohistochemistry staining, RT-PCR and western blot assay were taken for determining the expression levels of SMARCC1. And CCK-8, transwell assay, cell apoptosis assay, cell cycle analysis and subcutaneous tumor model were conducted to explore the role of SMARCC1 in carcinogenesis of bladder cancer. Results: In our experiments, Spearman’s correlation analysis, immunofluorescence staining and co-immunoprecipitation (Co-IP) assays showed that SMARCC1 interacted with KPNA2, and after knockdown of KPNA2, Nup50 and Nup153, the nuclear content of SMARCC1 decreased while the amount of SMARCC1 protein remaining in the cytoplasm increased, indicating that SMARCC1 could be transported into the nucleus via KPNA2 and thus acted as an oncogene. We found that both the mRNA and protein expression levels of SMARCC1 were increased in bladder cancer, and increased SMARCC1 expression was significantly associated with a higher T stage and poorer prognosis in bladder cancer patients. Knockdown of SMARCC1 slowed the growth of the two tested cell lines and clearly arrested the cell cycle at the G0/G1 phase checkpoint. Moreover, the migratory ability was significantly decreased and the number of apoptotic cells was increased. Conclusion: On the whole, our results demonstrate KPNA2, Nup50 and Nup153 regulate the process of SMARCC1 nuclear translocation in BC. SMARCC1 may be a competent candidate as a diagnostic and therapeutic target for BC. Further studies are required to research the mechanism and assess the role of SMARCC1 in vivo.